APPLICATION OF GAME-BASED LEARNING IN THROWING AND CATCHING LEARNING TO IMPROVE THE SOCIAL AND EMOTIONAL SKILLS OF ELEMENTARY SCHOOL STUDENTS - Muhammad Rizal Riswanda; Nurlailatun Ramdani; Lutfin Haryanto (Universitas Majalengka, 2025)
Social and emotional skills in elementary school students are often neglected in Physical Education, Sports, and Health subjects, because learning focuses more on motoric aspects. As a result, many students still have difficulty working together, regulating emotions, and maintaining sportsmanship when participating in physical activities. Different from previous studies that focused on improving motoric skills, this study focuses on social and emotional skills through the application of game-based learning in Physical Education, Sports, and Health. The purpose of this study is to describe the process of implementing game-based learning in learning to throw and catch a ball and its impact on the social and emotional skills of elementary school students. A descriptive qualitative approach was used in this study, with data collection techniques in the form of observation, interviews, and documentation. The subjects were fourth-grade students of SDN 2 Tente. The results showed that the application of game-based learning created an active, fun, and collaborative learning atmosphere. Active student participation increased from 63,3% to 93,3%, while the number of students who are easily angered decreased from 7 to 2 people, indicating a decrease in irritability levels of 71,4%. Improved social skills are evident in the ability to work together, communicate, and empathize, while improved emotional skills are evident in students' ability to manage emotions, accept defeat with sportsmanship, and support each other within the group. The teacher's role as a facilitator has proven crucial in guiding students in understanding character values ​​such as sportsmanship, empathy, and cooperation. Thus, game-based learning is not only effective in improving motor skills but also contributes significantly to improving students' social and emotional skills while presenting an innovative approach to Physical Education, Sports, and Health that integrates pedagogical and psychological aspects.